2010
DOI: 10.1021/cb1002366
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Relief of Botulinum Neurotoxin/A Intoxication with Aminopyridines: A New Twist on an Old Molecule

Abstract: Botulinum neurotoxins (BoNT) are the etiological agents responsible for botulism, a disease characterized by peripheral neuromuscular blockade and a characteristic flaccid paralysis of humans. BoNT/A is the most toxic protein known to man and has been classified by the Centers of Disease Control (CDC) as one of the six highest-risk threat agents for bioterrorism. Of particular concern is the apparent lack of clinical interventions that can reverse cellular intoxication. Efforts to uncover molecules that can ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 44 publications
(85 reference statements)
1
22
0
Order By: Relevance
“…It has been proposed that neuromuscular paralysis can be overcome by drugs that increase cholinergic neurotransmission (22,23). Indeed, we and other groups have shown that aminopyridines such as 3,4-diaminopyridine (3,4-DAP) transiently reverse muscle paralysis in a concentration-dependent manner (24)(25)(26)(27). 3,4-DAP is a selective potassium channel blocker that prolongs neuronal action potential duration, thereby increasing Ca 2+ influx through presynaptic voltage-gated Ca 2+ channels (28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that neuromuscular paralysis can be overcome by drugs that increase cholinergic neurotransmission (22,23). Indeed, we and other groups have shown that aminopyridines such as 3,4-diaminopyridine (3,4-DAP) transiently reverse muscle paralysis in a concentration-dependent manner (24)(25)(26)(27). 3,4-DAP is a selective potassium channel blocker that prolongs neuronal action potential duration, thereby increasing Ca 2+ influx through presynaptic voltage-gated Ca 2+ channels (28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…The U.S. Food and Drug Administration has approved 4-aminopyridine as a drug for the treatment of multiple sclerosis under the trade name Ampyra (Acorda Therapeutics, Inc., Hawthorne, NY) (Hauser and Johnston, 2010). Another aminopyridine compound, 3,4 diaminopyridine, is used in the treatment of botulism (Mayorov et al, 2010;Chalk et al, 2011) and Lambert-Eaton myasthenic syndrome (Keogh et al, 2011). A major limitation of the therapeutic use of these compounds is the harmful side effects that accompany their administration.…”
Section: Introductionmentioning
confidence: 99%
“…A major limitation of the therapeutic use of these compounds is the harmful side effects that accompany their administration. Indeed, guanidine consumption can cause bone marrow suppression and renal failure (Blumhardt et al, 1977), and aminopyridines can penetrate the blood-brain barrier and cause neurotoxicity (Mayorov et al, 2010). To overcome these detrimental side effects, it would be desirable to design analogs of aminopyridines and guanidines that exhibit high potency for their biological targets, enabling administration at low dosage levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 By synthesizing structural analogues, we hoped to discover more potent, yet, less toxic forms of the pharmacophore for treatment against BoNT intoxication. Previous reports indicate that 3,4-DAP and 4-AP, when administered at high doses, demonstrate toxicity issues such as seizures due to the molecules’ ability to penetrate the blood-brain barrier (BBB).…”
Section: Introductionmentioning
confidence: 99%